The Role of School Climate in Developing Student Self-Control in Middle School - Innani Qurrota Ainin NK (Konsultan Jurnal Ilmiah Indonesia, 2025)
The climate in junior high schools has a significant impact on shaping students' attitudes and self-regulation abilities. This study aims to examine the relationship between students' perceptions of the school environment and their ability to manage behaviour, particularly during the transitional period of adolescence and the influence of digital media. A supportive school environment is characterised by a sense of safety, positive social relationships, and beneficial interactions, which are believed to reduce negative behaviours such as bullying and enhance students' emotional intelligence. The approach of this study emphasises how students' perceptions of the school atmosphere can serve as an indicator of their emotional and social development. The highly dynamic period of adolescence requires students to have a supportive school environment so that they can effectively manage their emotions and behaviour. Findings from this study indicate that students' ability to self-regulate is strongly related to the quality of the school climate. Challenges from the use of technology and digital media also affect adolescents' ability to control themselves, making support through group discussions and self-management training necessary. Thus, a positive school environment becomes an important foundation for fostering positive behaviour and resilience in junior high school students.